Desain Penulisan Buku Ajar Bahasa Arab (Analisis Deskriptif Buku Al-‘Arābiyyah Baina Yadaik) - Muhammad Yusuf; Muhammad Ilham Akbar (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2018)
The strategic position of textbooks in Arabic learning is reflected in its role as a medium in transferring knowledge, ideology, and culture. Therefore giving attention to the primary principles in writing Arabic textbooks is a requirement. The realization of the socio-cultural, psychological, linguistic, and pedagogical basis in Arabic textbooks is not as easy as turning the palm. Many found writing designs that are